Grade 2 students’ conceptions about working with sharing - Sumpter, Lovisa; Eriksson, Helena; Hedefalk, Maria; Markkanen, Peter (LUMAT-B: International Journal on Math, Science and Technology Education, 2024)
The aim of this paper is to analyse and discuss grade 2 students’ conceptions about working with six cases describing different sharing scenarios. We interviewed 25 students, ages 8–9 years. Five different themes emerged in the thematic analysis. The first theme was about the importance of how to make sharing fair and that the cases were realistic. The second theme was about solutions being valid. The third theme covered conceptions about the cases as context or as concrete materials versus working in a textbook, which was connected to the fourth theme: to discuss and think versus being quiet. The fifth theme was about working at your desk versus the whiteboard. The results signal that open problems can alter students’ conceptions about mathematics but also challenges when creating spaces for such teaching.